Carbon nanotube field effect transistors and their possible applications - Yap, Weiyang. (2013)
This report focuses on growing of the carbon nanotubes (CNTs) under different various conditions using chemical vapour deposition technique and characterization is performed on the various grown CNTs. After characterization, the substrate together with the grown CNTs is further processed to produce a back-gated CNTFET. Testing of the various CNTFETs is then carried out to find out their performance due to the different growth condition.